Late quaternary glacial history of the La Ji Shan: Implications for the LGM on the northeastern Tibetan Plateau - Cui, Hang; Mou, Haizhen; Jing, Tao (Frontiers in Earth Science, 2023)
Previous studies have suggested that the Bayan Har Shan and Lake Donggi Cona areas on the northeastern Tibetan Plateau were not glaciated during the Last Glacial Maximum (LGM; MIS2). However, the La Ji Shan, which is at a lower elevation than the Bayan Har Shan and Lake Donggi Cona areas but has similar annual precipitation, experienced a glacial event during the LGM. To investigate this discrepancy, factors controlling glacier development in the Bayan Har Shan, Lake Donggi Cona, and La Ji Shan were examined. First, a coupled mass balance and ice ﬂow model was used to reconstruct the LGM climatic conditions in the La Ji Shan, and then the factors controlling glacier development were assessed based on the modeled LGM climatic conditions. With LGM precipitation being 70%–80% of present-day values, the modeled LGM temperature decrease was 3.9–4.3 °C, which is consistent with other reconstructed LGM climatic conditions on the Tibetan Plateau. A comparison of the topography and climate of the La Ji Shan, Bayan Har Shan and Lake Donggi Cona areas indicates that a lower LGM summit height above the LGM equilibrium line altitude (ELA) and LGM annual precipitation at the LGM ELA are the main reason for the lack of LGM glacial expansion in the Bayan Har Shan and Lake Donggi Cona areas.